Experimental and numerical simulation study on coupling tripping of partial trapezoidal threaded casing head and casing coupling - Zhang, Jun; Ding, Chao; Li, Yanan; Dong, Hai; Ayala, Madi; Li, Mingzhi (Frontiers in Materials, 2024)
Casing connection is a common connection method in oil and gas reservoir production, and the tripping of casing will seriously hinder the production process. In order toTo study the casing tripping process and the minimum tensile load required for casing tripping under different loosening buckle states, three kinds of casing tripping tensile tests were carried out. The thread morphology of the casing head and casing coupling was analyzed by local cutting at the end of the experiment, and the thread failure area was analyzed by scanning electron microscope, and then other loosening states were studied and analyzed by means ofusing numerical simulation. The research results show that as the number of loosening buckle buckles increases, the minimum tensile load required for the casing head and casing coupling to trip decreases. The observation of the thread shape shows that the thread part of the casing head was seriously damaged. Scanning electron microscopy results show that the fracture mode at the thread of the casing head is ductile fracture. Numerical simulation results show that the maximum stress area during the tripping process is at the contact position between the thread heads. Based on the experimental and numerical simulation results, the relationship between the number of casing loosening and the minimum tensile load required for casing tripping is obtained. The research results can be used as the experimental and theoretical basis for the investigation of casing tripping accidents, and can also provide experimental reference for the design of the next generation of casing.